ANÁLISIS DE LA CONCILIACIÓN TRIBUTARIA Y SU INCIDENCIA EN EL IMPUESTO A LA RENTA, DE LA COMPAÑÍA INDUSTRIA PLÁSTICA INPLASBAN S.A, EN LA CIUDAD DE DURÁN - Romoleroux Zuñiga, Richard Benjamín (2016)
The purpose of this study is the Tax Conciliation Analysis and its impact on the income tax of the company INDUSTRIA PLASTICA INPLASBAN SA, in the city of Durán, which focuses on the variations that generate deductible and non-deductible expenses, as contrasted with the company's internal accounting policies. It is a matter of summarizing the application of the tax benefits to this type of companies, strengthening their knowledge through the use of the legal basis. Once the information was obtained, a deductive methodology was developed with a quantitative approach that allowed to evaluate the two periods 2014 and 2015 and whose results were able to determine the impact generated that is summarized in an inadequate management of the deductible expenses, which increases the Payment of the tax, this study allowed the optimization of the benefits described in the LORTI income purification and the tax conciliation, when applied correctly.